2022
DOI: 10.1002/suco.202100649
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of square concrete‐filled double‐skin tubular columns with outer stainless‐steel tube

Abstract: Stainless steel has increasingly been utilized in concrete‐filled composite columns because of its high corrosion resistance and aesthetic appearance. However, there is little published information on the structural behavior of concrete‐filled double‐skin steel tubular (CFDST) columns made of square outer stainless‐steel skin and circular inner carbon steel tubes. The present study focuses on the nonlinear analysis of axially loaded CFDST short columns with outer square stainless steel tube and inner circular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the selection of element types, for concrete columns with spiral reinforcement, concrete as well as FRP reinforcement are assigned C3D8R "an 8-node linear brick, reduced integration, hourglass control". 50,52,[65][66][67][68][69][70]…”
Section: Meshing and Selection Of Element Typementioning
confidence: 99%
“…In the selection of element types, for concrete columns with spiral reinforcement, concrete as well as FRP reinforcement are assigned C3D8R "an 8-node linear brick, reduced integration, hourglass control". 50,52,[65][66][67][68][69][70]…”
Section: Meshing and Selection Of Element Typementioning
confidence: 99%
“…Concrete‐filled steel tubular (CFST) columns are widely utilized in various modern building structures, especially in high‐rise buildings, owing to their excellent structural performance, which includes large energy‐absorption capacity, high ductility and stiffness 1–4 . As a member of the CFST column family, recently, an innovative composite column referred to as concrete‐filled double‐skin steel tubular (CFDST) columns with concrete infilled between the two centric tubes has captured the interests of researchers 5–9 .…”
Section: Introductionmentioning
confidence: 99%
“…performance, which includes large energy-absorption capacity, high ductility and stiffness. [1][2][3][4] As a member of the CFST column family, recently, an innovative composite column referred to as concrete-filled double-skin steel tubular (CFDST) columns with concrete infilled between the two centric tubes has captured the interests of researchers. [5][6][7][8][9] The flexural stiffness and fire resistance of CFDST columns are higher compared to CFST columns.…”
mentioning
confidence: 99%
“…However, both the studies 14–18 and engineering practices on the axial compression mechanical behavior of the ordinary SCFST columns have shown that the smaller the tube wall width‐to‐thickness ratio was, the higher the bearing capacity and ductility were. However, it is still unknown‐‐whether increasing the tube wall thickness or setting longitudinal stiffeners could directly constrain core concrete and effectively improve the bearing capacity and ductility.…”
Section: Introductionmentioning
confidence: 99%